Peran Kepala Madrasah dalam Membina Kinerja Guru di MI Plus Istiqomah Kecamatan Ambulu Kabupaten Jember - Agus Zainudin; Fauzan Anshori (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2023)
This study used by qualitative research methods. The informants in this case where the principal and the teachers at the madrasah. Which can be used as further information providers such as administrative staff and students. Data collection techniques used in this study were through observation, interviews, and documentation. This study used data collection techniques that were carried out by observation, interviews and documents. Qualitative data analysis. The results of the study show that (1) the role of the principal in fostering teachers at MI Plus Istiqomah, Ambulu Subdistrict, is as follows (a) The actions of the Head of Madrasah Ibtidaiyah Plus Istiqomah in empowering the teacher council by always advising teachers to always be enthusiastic in carrying out teaching and learning activities. (b) The Principal of Madrasah Ibtidaiyah Plus Istiqomah does not tolerate delays in completing assignments and work. The Madrasah head always sets a deadline and requires all teachers to comply with the set time. The Madrasah head also provides direction and guidance and helps teachers to use the facility. (2) Obstacles to the role of the Madrasah Head in fostering teacher performance at MI Plus Istiqomah are related to: (a) Lack of facilities and infrastructure to carry out every decision that has been made. (b) Low skills, especially computer mastery. (c) The responsibility of the teacher council can still be said to be low in carrying out the mandate given by the Madrasah Head. (3) Solutions to overcome obstacles in fostering teacher performance at MI Plus Istiqomah Ambulu District are carried out by involving school residents, parents of students, the government and various parties concerned with collaborative education. This is necessary to monitor the development of students in the learning process, including in the intellectual realm and psychological.